GAMBARAN FAKTOR PENYEBAB KEJADIAN IKTERIK PADA BAYI DI RUANG NICU RUMAH SAKIT UNIVERSITAS MATARAM - Romadonika, Fitri; Adithia Pratiwi, Eka; Nurul Hidayati, Baiq; Pratiwi Safitri, Rias (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2024)
ABSTRACT Jaundice or jaundice is a change in color to yellow that occurs in neonates or newborns in the sclera of the eye, mucosa and skin due to increased bilirubin levels in the blood. The impact of the factors that cause jaundice in babies is that if bilirubin levels increase excessively and are not excreted by the body, babies are more at risk of becoming deaf, suffering from cerebral palsy, brain damage (kernicterus) and even death. The factors that cause jaundice can come from maternal, perinatal and neonatal factors. The incidence of neonatal jaundice at the University of Mataram Hospital ranks second after BBLR. The purpose of the study was to find out the description of the factors that cause jaundice in infants in the NICU Room of the University of Mataram Hospital. The design of this study is descriptive. The population is all infants aged 0-28 days with sampling techniques using purposive sampling. The results of this study were obtained that the factors that cause neonatal jaundice in maternal factors with a gestational age of aterm (<37 weeks) were obtained (55.9%).The perinatal factor, namely the type of delivery carried out by SC (Section Caesarean) as much as (58.8%). The neonatal factor is low birth weight (BBLR) (52.9%). It is hoped that parents can find out the signs and symptoms of jaundice as early as possible and immediately take them to a health service facility to minimize the occurrence of jaundice complications. Keywords: Jaundice, Maternal, Perinatal, Neonatal